PENGELOLAAN KEUANGAN DIGITAL UNTUK PEMULA: CARA CERDAS MENGATUR KEUANGAN DI ERA TEKNOLOGI - Fitria, Giawan Nur; Pernamasari, Rieke (Universitas Islam 45 Bekasi, 2025)
This program was implemented in Kembangan Utara, West Jakarta, an area characterized by heterogeneity, dense population, and a significant proportion of low-income residents. The primary objective of this initiative was to enhance the skills and digital financial literacy of Micro, Small, and Medium Enterprises (MSMEs), particularly housewives, through training on the use of the Buku Warung application. The main challenges faced by the community included low household income, limited knowledge of financial planning, and minimal access to appropriate technology for business management. The program employed a participatory approach encompassing outreach sessions, hands-on training, application demonstrations, and questionnaire-based evaluations. Implementation was carried out in several stages: participant identification, dissemination of financial management concepts, practical training on the use of the Buku Warung application, and monitoring and evaluation sessions. The activity involved 40 participants and was held at the RPTRA (Child-Friendly Integrated Public Space) Kembangan, West Jakarta. The results indicated that participants were able to understand and apply basic digital financial recording techniques. The evaluation further demonstrated that the program was aligned with community needs and was considered effective in terms of both content and delivery methods. This initiative had a positive impact on improving participants’ digital skills while promoting financial inclusion. To ensure sustainability, it is recommended that the program be followed by intensive mentoring, advanced training, and the provision of supporting facilities to strengthen community business capacity and contribute to local economic development.